2018
DOI: 10.1101/461723
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prefrontal cortical ChAT-VIP interneurons provide local excitation by cholinergic synaptic transmission and control attention

Abstract: SummaryNeocortical choline acetyltransferase (ChAT)-expressing interneurons are a subclass of vasoactive intestinal peptide (ChAT-VIP) neurons of which circuit and behavioural function are unknown. It has also not been addressed whether these neurons release both neurotransmitters acetylcholine (ACh) and GABA. Here, we find that in the medial prefrontal cortex (mPFC), ChAT-VIP neurons directly excite interneurons in layers (L)1-3 as well as pyramidal neurons in L2/3 and L6 by fast cholinergic transmission. Dua… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 59 publications
(99 reference statements)
1
28
2
Order By: Relevance
“…A recent publication reported rates of GABA and ACh connectivity from cortical ChAT + neurons that were strikingly different from what we described above 28 . They reported that optogenetic activation of cortical ChAT + neurons frequently resulted in postsynaptic cholinergic currents and rarely GABAergic currents.…”
Section: Resultscontrasting
confidence: 94%
See 3 more Smart Citations
“…A recent publication reported rates of GABA and ACh connectivity from cortical ChAT + neurons that were strikingly different from what we described above 28 . They reported that optogenetic activation of cortical ChAT + neurons frequently resulted in postsynaptic cholinergic currents and rarely GABAergic currents.…”
Section: Resultscontrasting
confidence: 94%
“…Target-specificity is partially specified at the pre-synaptic level, as we identified two distinct populations of pre-synaptic terminals: a subset that are competent to release both GABA and ACh and others that can only release GABA. The second class of cortical ChAT + interneurons is molecularly and functionally distinct from VIP + cholinergic interneurons and was discovered in an effort to reconcile our results with those of another study that described predominantly ACh, and not GABA release, from cortical ChAT + interneurons 28 . This sparse population of non-VIP ChAT + neurons is found in the mPFC, has a distinct developmental origin from VIP interneurons, and contributes primarily cholinergic signaling.…”
Section: Introductionmentioning
(Expert classified)
See 2 more Smart Citations
“…Sst-Chod1, Sst-Calb2-Pdlim5, Sst-Chrna2-Glra3) are also consistent with previous studies (Figure 1) (18)(19)(20). Certain clusters may correspond to newly discovered types; for example, one of the four clusters defined by VIP and Chat expression might correspond to a type that directly excites layer 1 interneurons and layer 2/3 pyramidal neurons (21).…”
Section: High Throughput Single Cell Analyses Toward Classification Amentioning
(Expert classified)